Features of folate cycle disorders in children with ASD - Maltsev, DmitryV (Bangladesh Journal of Medical Science, 2020)
Aim: to show the effect of genetically determined folate cycle deficiency in children with autism spectrum disorders (ASD). Participants: 89 children (57 boys; 32 girls, Ukraine, 2-10 years old); participants were diagnosed with ASD. The control group consisted of 34 children with ASD. Diagnostic methods:polymerase chain reaction (PCR), complex immunological research, diagnosis of infection, determination of biomarkers. Results and discussion:Hyperhomocysteinemia was revealed in 87% of cases (p <0.05; Z <Z0.05).The indicated form of immunodeficiency was noted among 91% participants in the study, while only in 27% children of the control group had a similar immunological phenotype.The serum concentration of folic acid was increased in 64%, and reduced in 21% of cases. An increase of vitamin B12 also occurred in 64%, and vitamin B6 - only in 43% of cases. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.737-742